2011
DOI: 10.1088/0953-8984/23/25/255402
|View full text |Cite
|
Sign up to set email alerts
|

A dipole polarizable potential for reduced and doped CeO2obtained from first principles

Abstract: In this paper we present the parameterization of a new interionic potential for stoichiometric, reduced and doped CeO 2 . We use a dipole polarizable potential (DIPPIM: the dipole polarizable ion model) and optimize its parameters by fitting them to a series of density functional theory calculations. The resulting potential was tested by calculating a series of fundamental properties for CeO 2 and by comparing them against experimental values. The values for all the calculated properties (thermal and chemical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
68
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 62 publications
4
68
0
Order By: Relevance
“…1 show visually the increase in localization of 4f electron charge density around a Ce cation (with one neighbour vacancy) with increasing U. Charge localization was also confirmed by the projected spin density, 14 which is close to one for the Ce cation when U Z 5 eV (see Table I in Supporting Materialw). It is clear that charge localization strongly affects the chemical expansion coefficient, with a 74% increase from delocalized (U = 0 eV) to completely localized (U = 6 eV).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…1 show visually the increase in localization of 4f electron charge density around a Ce cation (with one neighbour vacancy) with increasing U. Charge localization was also confirmed by the projected spin density, 14 which is close to one for the Ce cation when U Z 5 eV (see Table I in Supporting Materialw). It is clear that charge localization strongly affects the chemical expansion coefficient, with a 74% increase from delocalized (U = 0 eV) to completely localized (U = 6 eV).…”
mentioning
confidence: 57%
“…12 Additionally, doped ceria is being investigated as the solid electrolyte in intermediate to low temperature SOFCs, where the non-stoichiometry induced chemical expansion can lead to mechanical failure. 13 Recently, we studied the origin of chemical expansion in CeO 2Àd 10,14 (relying on Shannon's ionic radii, a valid assumption for this system 15 ), and found that upon reduction (increase in d), chemical expansion arises from two competing mechanisms: (1) an increase in lattice volume upon increase in Ce radius (i.e. Ce 4+ -Ce 3+ ) and (2) a decrease in lattice volume with the formation of charge compensating oxygen vacancies.…”
mentioning
confidence: 99%
“…For Ce a U parameter of 5-7 eV is commonly used. [30][31][32][33] In this study, we therefore choose U = 5 eV and J = 0 eV. 34 Spin polarized calculations are performed to be consistent with experimental findings 35,36 and experimental lattice constants of 5.413 Å, 5.423 Å, 5.431 Å, 5.422 Å, 5.476 Å, and 5.411 Å are taken from Y, 37 Gd, 38 Sm, 39 Pr, 40 and La 38 doped CeO 2 and pure CeO 2 , 25 respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The rst one is the formation of an oxygen vacancy, with surrounding lattice contraction (primarily due to electrostatic interactions), and the second is a change in the cation radius, resulting in lattice expansion (primarily due to steric effects), 15,16 with the latter contribution much larger than the former and thus resulting in a net expansion upon reduction of the material. The importance of charge localization was also recognized in a subsequent study.…”
Section: Broader Contextmentioning
confidence: 99%